Receiver Operating Characteristic Analysis and Clinical Trial Simulation to Inform Dose Titration Decisions. (15th October 2018) - Clements, John David; Perez Ruixo, Juan Jose; Gibbs, John P.; Doshi, Sameer; Perez Ruixo, Carlos; Melhem, Murad
Abstract : Optimal dose selection in clinical trials is problematic when efficacious and toxic concentrations are close. A novel quantitative approach follows for optimizing dose titration in clinical trials. A system of pharmacokinetics (PK), pharmacodynamics, efficacy, and toxicity was simulated for scenarios characterized by varying degrees of different types of variability. Receiver operating characteristic (ROC) and clinical trial simulation (CTS) were used to optimize drug titration by maximizing efficacy/safety. The scenarios included were a low‐variability base scenario, and high residual (20%), interoccasion (20%), interindividual (40%), and residual plus interindividual variability scenarios, and finally a shallow toxicity slope scenario. The percentage of subjects having toxicity was reduced by 87.4% to 93.5%, and those having efficacy was increased by 52.7% to 243%. Interindividual PK variability may have less impact on optimal cutoff values than other sources of variability. ROC/CTS methods for optimizing dose titration offer an individualized approach that leverages exposure‐response relationships.